(untitled) (Bangladesh Journal of Animal Science, 2014)
Madura cattle are indigenous in Madura Island of Indonesia, which are raised for beef/ draught, racing (karapan) and beauty contest (sonok). The purpose of this study is to determine the farmer income of beef/ draught cattle, racing bull and contest cows business in Madura Island, and to determine which business gives the greatest advantage to the farmers. This study involved 240 beef cattle farmers, 135 racing bull farmers and of 145 beauty contest cows farmers from all over Madura Island. Data collected were analysed for fixed costs, variable costs, total costs, revenue, income, benefit-cost ratio (B/C ratio). The results showed that the average income/head/year in beef/draught, racing and beauty contest cattle were IDR. 6,698,017; IDR. -8,218,347; and IDR. 447,880, respectively. The average value of B/C ratio in the beef/draught cattle business, racing bull and cow contest were -0.51, -0.20 and 0.04, respectively. It is concluded that cow contest business has the best advantage based on the aspects of farmer’s income and B/C ratio. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19388 Bang. J. Anim. Sci. 2014. 43 (1): 68-73